1999
DOI: 10.1161/01.str.30.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Serum Glucose Level and Diabetes Predict Tissue Plasminogen Activator–Related Intracerebral Hemorrhage in Acute Ischemic Stroke

Abstract: Background and Purpose —Five pretreatment variables ( P <0.1 univariate analysis), including serum glucose (>300 mg/dL), predicted symptomatic intracerebral hemorrhage (ICH) in the National Institute of Neurological Disorders and Stroke rtPA trial. We retrospectively studied stroke patients treated <3 hours from onset with intravenous rtPA at 2 institutions to evaluate the role of these variables in predicting ICH. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
221
2
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(245 citation statements)
references
References 61 publications
13
221
2
8
Order By: Relevance
“…t-PA itself activates MMP-9 and thus may promote hemorrhagic transformation. Hyperglycemia and diabetes have also been associated with elevated MMP-9 and the development of hemorrhagic transformation [81]. {Uemura, 2001 #2927 BBB disruption independently correlates with serum MMP9 levels [82].…”
Section: Biomarkers Of Hemorrhagic Transformationmentioning
confidence: 99%
“…t-PA itself activates MMP-9 and thus may promote hemorrhagic transformation. Hyperglycemia and diabetes have also been associated with elevated MMP-9 and the development of hemorrhagic transformation [81]. {Uemura, 2001 #2927 BBB disruption independently correlates with serum MMP9 levels [82].…”
Section: Biomarkers Of Hemorrhagic Transformationmentioning
confidence: 99%
“…Nevertheless, hyperglycaemia has a particularly potent adverse effect after thrombolysis, also in patients with diabetes [23]. Hyperglycaemic patients more commonly develop intracerebral hemorrhage after thrombolysis and have overall poorer clinical and radiological outcome [24]. Hyperglycaemic patients are also less likely to recanalise with thrombolysis.…”
Section: Stroke-associated Hyperglycaemiamentioning
confidence: 99%
“…Some studies have reported an increased risk of symptomatic intracranial hemorrhage (sICH) after tPA treatment in patients with diabetes or hyperglycemia,8, 9, 10 and admission glucose has been used in prognostic models to identify patients at risk of sICH after tPA 11. Even though studies did not find overall reduced benefit of tPA in diabetic patients,12 decreased rates of tPA administrations are observed in diabetic patients 13.…”
Section: Introductionmentioning
confidence: 99%